Sea plants - Bourgougnon, Nathalie; Arata, Paula Ximena (Advances in botanical research, 2014)
Advances in Botanical Research publishes in-depth and up-to-date reviews on a wide range of topics in plant sciences. The series features several reviews by recognized experts on all aspects of plant genetics, biochemistry, cell biology, molecular biology, physiology and ecology. This thematic volume, number 71, features reviews on sea plants. Its chapters cover topics such as the role of algae in sustainability; the status of kelp exploitation and marine agronomy; potential applications for enzymatic recovery of metabolites from seaweeds; and many more.